Toddler Feeding Mode And Toddler Eating Behaviour - Rahmi Nurrasyidah; Lutfiana Puspita Sari (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2026)
The role of mothers is very important in introducing and getting used to healthy foods. Prevention and treatment of stunting are related to the habituation of healthy foods from an early age. Mothers' strategies in providing food need to be studied for their influence on toddlers' eating behavior. Objective: This study was designed to determine the relationship between toddler feeding modes and toddler eating behavior. Research methodology: This study was an observational study with a cross-sectional design involving 60 mothers of toddlers. Exclusion criteria were mothers with toddlers suffering from congenital diseases, developmental disorders, infectious diseases treated in hospitals, malignant diseases, and incomplete questionnaires. Primary data collection included respondent characteristics and feeding methods using the Caregiver's Feeding Styles Questionnaire (CFSQ). Toddler eating behavior was measured using the Infant and Child Feeding Questionnaire (ICFQ) and the Children Eating Behavior Questionnaire (CBEQ) food fussiness subsection. Analysis using the Chi Square test. Results: The study found no relationship between feeding modes and picky eating behavior in toddlers where p Value >0.005. There is no relationship between feeding mode and eating behavior in toddlers associated with eating disorders, with a p-value of >0.005. Conclusion : There is no relationship between feeding mode and toddlers' eating behavior. Researchers recommend further research with a larger sample size and a case-control design to avoid research bias.